Influência da terapia estrogênica sobre marcadores imunes e sobre a resposta à vacina contra a influenza em mulheres na pós-menopausa - Itaborahy, Rejane Martins Ribeiro (2016)
To evaluate the effect of estrogen therapy on cellular and humoral immune markers in postmenopausal women. Study design Prospective intervention controlled study (estradiol 1 mg, for 14–17 weeks), evaluating counting and immunophenotyping of different types of leukocytes, concentration of immunoglobulins and cytokines INFγ, IL-6, IL-17, IL-4 and IL-10 in the peripheral blood, before and after the estrogen therapy in 58 postmenopausal women. Methods The leukocyte count was measured by an automated hematology analyzer. The counts and immunophenotyping of T lymphocytes were determined by flow cytometry. Immunoglobulin E was measured by electrochemiluminescence and immunoglobulins A, G, and M were measured by nephelometry. The simultaneous quantification of multiple cytokines by chemiluminescence was used to measure the serum concentration of IFN-γ, IL-4, IL-6, IL-10 and IL-17. Results The comparison of hematological cellular components, evaluated before and after the use of estradiol, revealed that the values remained unchanged. The serum concentrations of the different immunoglobulins G, M, E, A, and cytokines remained stable throughout the 14 to 17 weeks of follow up. Conclusion Isolated estrogen therapy in postmenopausal women did not modify any of the cellular and humoral immune markers, after the use of 1 mg of estradiol for 14 to 17 weeks.